Territorial behaviour, forced copulations and mixed reproductive strategy in ducks - Gauthier, Gilles (Wildfowl, 1988)
Ducks (sub-family Anatinae) exhibit considerable variability in their degree of territoriality and in the occurrence of extra-pair forced copulations. A model is proposed to explain this variability. Current evidence suggests that territorial behaviour in ducks is closely associated with mate defence. The degree of territoriality is also inversely related to the frequency of forced copulations, and there is good evidence that forced copulation is a secondary mating tactic of paired males and part of a mixed reproductive strategy. Furthermore, strongly territorial species are restricted to stable habitats. Based on this evidence, it is hypothesised that variability in the nesting success of females, and therefore in the expected reproductive success of paired males, determines whether males will engage in a mixed reproductive strategy or exhibit a strong territorial system. In stable habitats, the probability that a male's mate will produce some offspring is high in most years, and males should therefore strongly guard their mate and not actively engage in forced copulation. In variable habitats, the risk of nest failure is high and the variance in male reproductive success will be greater. However, because the variance in male reproductive success will be reduced if they inseminate several females, mate guarding should be weak in these males and they should pursue a mixed reproductive strategy by actively seeking forced copulations.